Psoriasis and osteoporosis - Gerkowicz, Agnieszka; Pietrzak, Aldona; Nogalski, Adam; Lűbek, Tomasz; Wawrzycki, Bartłomiej; Kowalczyk, Karolina; Makara-Studzińska, Marta; Chodorowska, Grażyna; Paszkowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2013)
Hormones are known to be an important factor influencing many crucial physiological processes in the human body. Bone metabolism is a good example of such regulatory contribution of hormones. Sex hormones like estrogens and androgens, growth hormone or calcitonin support bone growth. On the other hand, parathormone and corticosteroids may induce osteoporosis. Osteoporosis is a systemic skeletal disease characterized by architectural deterioration of bone tissue and low bone mass, which results in increased bone fragility. Postmenopausal osteoporosis is the most common type of involutional osteoporosis. The connection between menopause and loss of bone mass has attracted attention of the scientific community for many years and has been intensively investigated. There is little known about influence of psoriasis on bone metabolism. Psoriasis is a chronic and relapsing skin disease with a population prevalence of 2-3%. It is characterized by immunological dysfunction, epidermal hyperproliferation, impaired differentiation of keratinocytes and excessive angiogenesis. In recent years, psoriasis has been recognized as a disease associated with systemic comorbidities. Data about the possible association between reduced mineral bone density and psoriasis are limited. Modern conceptions implying such connection are mainly based on common inflammatory factors like tumor necrosis factor α (TNF-α) or IL-6, which are involved in pathophysiology of both psoriasis and osteoporosis.